Development of simulation tests to assess the fate of Unilever ingredients under untreated discharge conditions - Finnegan, Chris J. (Cranfield University, 2007)
Unilever product ingredients are discharged into the environment via a number of routes, in many regions of the world there is a lack of municipal waste water treatment and the discharge of chemicals directly into the environment in the presence of untreated sewage is a major pathway. An absence of data on the behaviour of the fate and effects of chemicals under such conditions requires overly stringent and unrealistic assumptions when assessing risk (e.g. no biodegradation is assumed). Traditional risk assessment fails since water quality is compromised by pollutants associated with raw sewage (e.g. BOD and ammonia) and the relevance of the ‘standard’ risk assessment approach has thus been questioned. An alternative risk assessment model, based on the ‘impact zone’ concept, has been proposed for direct discharge conditions. In this model, chemicals are assessed in terms of their predicted environmental concentration (PEC) at the end of an impact zone, within which the ecosystem is impacted by the pollutant, free ammonia, and beyond which it is not. Linear alkylbenzene sulphonate (LAS) was used a model compound to understand the fate of materials classified as readily biodegradable in this scenario. Batch and dynamic test systems simulating conditions associated with untreated discharge, confirmed that LAS was degraded quicker than the general organics present in settled sewage and that beyond the defined ‘impact zone’ it is extensively removed. Predicted no effect concentrations (PNECs) can also be generated for chemicals on the inhibition of key microbial processes (biological oxidation and nitrification) which are essential in rivers for self purification. A variety of detergent ingredients (ranging from readily biodegradable to anti-bacterial) were investigated in short term toxicity tests. The tests produced a range PNECs and confirmed that these ingredients can show selective inhibition towards heterotrophic or autotrophic bacterial populations. All of the PNECs generated were above the PEC for these ingredients.